2008
DOI: 10.1097/01.ccm.0000292015.16171.6d
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol is associated with mortality in critically ill trauma and surgical patients

Abstract: Objective: Sexual dimorphism (variation in outcome related to sex) after trauma-hemorrhage and sepsis is well documented in animals, with the pro-estrus state being proinflammatory and associated with a survival advantage. Although some observational studies confirm this pattern in humans, others demonstrate no difference in mortality. Estrogens are important modulators of the inflammatory response and insulin resistance in humans and have been linked to increased mortality during sepsis. Our objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 62 publications
2
74
0
3
Order By: Relevance
“…30,31 In our study characterizing serum hormones acutely after TBI, elevated estradiol in particular was associated with mortality and poor outcomes 6 months postinjury. 10 These findings suggest that tissuespecific aromatase activity significantly influences the hormone profiles, and there are different mechanisms of hormone physiology at play in the CSF versus serum compartments.…”
Section: Garringer Et Almentioning
confidence: 99%
“…30,31 In our study characterizing serum hormones acutely after TBI, elevated estradiol in particular was associated with mortality and poor outcomes 6 months postinjury. 10 These findings suggest that tissuespecific aromatase activity significantly influences the hormone profiles, and there are different mechanisms of hormone physiology at play in the CSF versus serum compartments.…”
Section: Garringer Et Almentioning
confidence: 99%
“…5,15,23,25,29 However, this presumed benefit has not been consistently translated from animal (rodent) models to patients in clinical trials, partly due to a difference between the two groups in production of Eg via peripheral aromatization, which is selectively present in primates only. 5,15,23,25,29 Up to 80% of patients with sTBI have suppression of the hypothalamic-pituitary-gonadal axis and activation of stress hormones produced by the adrenal gland; therefore, Eg production is predominantly under the control of peripheral aromatization in adipose tissue, which in turn is positively affected by proinflammatory cytokines like TNF-a. 29 Because there is a surge of systemic proinflammatory chemokines immediately following sTBI, the injury increases Eg levels as a byproduct of ongoing inflammatory response, thereby reflecting a global illness rather than a causal role.…”
Section: Gonadal Hormonesmentioning
confidence: 99%
“…29 Because there is a surge of systemic proinflammatory chemokines immediately following sTBI, the injury increases Eg levels as a byproduct of ongoing inflammatory response, thereby reflecting a global illness rather than a causal role. 5,29 Few studies have shown a capacity of serum Eg levels at 48 hours to predict mortality, 5,15 but their model failed to incorporate proinflammatory cytokines, a major confounder in the primate TBI model. As expected, we failed to observe any statistically significant impact of admission Eg levels on mortality in the adjusted binary logistic model, despite a weak association evident with survival status (p = 0.09 and p = 0.07 at 6 and 12 months, respectively).…”
Section: Gonadal Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also found that increased levels of estrogens are especially marked in males with sepsis (Fourrier et al, 1994;Majetschak et al, 2000). In addition, high circulating levels of estrogens seem efficient predictors of death in sepsis (Christeff et al, 1988;Dossett et al, 2008;May et al, 2008). The mortality of elderly patients with severe infections is related to increased estradiol levels in both men and women, whereas increased testosterone levels are found in females who do not survive (Angstwurm et al, 2005).…”
Section: Infection Due To Intracellular Bacteria Sex Ratio Referencementioning
confidence: 99%